2018
DOI: 10.1080/17461391.2018.1444095
|View full text |Cite
|
Sign up to set email alerts
|

Physiological implications of preparing for a natural male bodybuilding competition

Abstract: This study aimed to describe the body composition and physiological changes which take place during the in-season and recovery periods of a group of natural bodybuilders. Natural male bodybuilders (n = 9) were assessed 16 (PRE16), 8 (PRE8), and 1 (PRE1) week(s) before, and 4 (POST4) weeks after a bodybuilding competition. Assessments included body composition, resting metabolic rate (RMR), serum hormones, and 7-day weighed food and training diaries. Change in parameters was assessed using repeated-measures ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 48 publications
6
78
1
Order By: Relevance
“…These findings are consistent with previous findings in bodybuilders, whereby fat mass was significantly reduced in PreC and FFM was preserved (Bamman et al, 1993;Mäestu et al, 2010;Mitchell et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous findings in bodybuilders, whereby fat mass was significantly reduced in PreC and FFM was preserved (Bamman et al, 1993;Mäestu et al, 2010;Mitchell et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Bodybuilding is a sport in which competitors are judged by their muscular appearance, presenting characteristics that include extreme muscular development, very low levels of body fat, and symmetrical physiques (Helms et al, 2014). Bodybuilders generally employ two distinct phases in their preparation: "Off season" (OffS), whereby the main focus is on maximizing muscle hypertrophy and body mass gain, achieved primarily through altered training volumes combined with a hypercaloric diet and positive energy balance (Spendlove et al, 2015;De Moraes et al, 2017); and a pre-competitive period (PreC), lasting from 9 to 26 weeks before the competition (Rossow et al, 2013;Mitchell et al 2018), when athletes focus on reducing body fat stores while maintaining fat-free mass levels specific to competing in a given weight class. In this phase, bodybuilders enter a negative energy balance, usually brought about by elevations in training volume, inclusion of aerobic activity and the use of restrictive diets (Bamman et al, 1993;Newton et al, 1993;Helms et al, 2014;Spendlove et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-competition phase, the majority of athletes attempt to reduce body fat levels and preserve LBM using a combination of rigorous resistance and aerobic training, while manipulating their nutritional intake to achieve a negative energy balance (Hackett et al, 2013;Petrizzo et al, 2017). The precompetition phase lasts between 12 and 24 weeks (Mitchell et al, 2018) and athletes are likely to compete between two to three times per year . Usually, the pre-competition phase is followed by a recovery phase (a transition to off-season), during which athletes increase their total energy intake and decrease their total training load (Hulmi et al, 2016).…”
Section: Body Composition In Competitionmentioning
confidence: 99%
“…Corroborating, Mitchell, et al [21], analyzed natural male bodybuilders, their results showed a large reduction in total and free testosterone and Insulin-like Growth Factor-1 (IGF-1) occurred between PRE16 and PRE1 (weeks of training before competition). The authors comment about the reduction in anabolic hormone concentration is likely attributable to the prolonged negative energy balance, despite a high dietary protein intake, the same nutritional strategies adopted for our participants.…”
Section: Nutritionmentioning
confidence: 97%